2016
DOI: 10.1167/iovs.16-19291
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Berberine on Oxidized LDL-Induced Cytotoxicity to Human Retinal Müller Cells

Abstract: PurposeLimited mechanistic understanding of diabetic retinopathy (DR) has hindered therapeutic advances. Berberine, an isoquinolone alkaloid, has shown favorable effects on glucose and lipid metabolism in animal and human studies, but effects on DR are unknown. We previously demonstrated intraretinal extravasation and modification of LDL in human diabetes, and toxicity of modified LDL to human retinal Müller cells. We now explore pathogenic effects of modified LDL on Müller cells, and the efficacy of berberine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 54 publications
(89 reference statements)
1
35
0
Order By: Relevance
“…Evidence suggests that the status of retinal neuronal structure and vasculature can reflect that of the cerebral nervous system [211]. Our literature survey revealed that berberine could prevent diabetic retinopathy [64][65][66]. Although the mechanistic link between retinal injuries and cognitive dysfunction is not clear, these data support that berberine could prevent diabetes-associated damages to the neuronal network in the central nervous system, including retina.…”
Section: Retinal Protectionmentioning
confidence: 56%
See 2 more Smart Citations
“…Evidence suggests that the status of retinal neuronal structure and vasculature can reflect that of the cerebral nervous system [211]. Our literature survey revealed that berberine could prevent diabetic retinopathy [64][65][66]. Although the mechanistic link between retinal injuries and cognitive dysfunction is not clear, these data support that berberine could prevent diabetes-associated damages to the neuronal network in the central nervous system, including retina.…”
Section: Retinal Protectionmentioning
confidence: 56%
“…As shown in Table 8, berberine protected retinal Müller cells from HG-and LDL-induced damage via enhancing AMPK signaling [65,66] and prevented retinal endothelial injuries induced by HGactivated leukocytes [64].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…RPE cells migrate to the vitreous body, promote secretion of a large amount of inflammatory cytokines and facilitate the secretion of ECM, ultimately leading to ECM reconstruction and the development of retinal detachment (24,25). RRD is an inflammatory pathological process, in which a tear forms on the lower surface of retina or at the interface between the vitreous body and the retina, and leads to further secretion of inflammatory cytokines, including IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…This factor can be primarily secreted by MGCs after prolonged exposure to high levels of glucose and fatty acids (oleic and linoleic acid), two harmful stimuli frequently observed in the metabolic syndrome (Capozzi et al., ). In this inflammatory environment, ROS levels are increased and they oxidize low‐density lipoprotein molecules, which have been shown to increase VEGF synthesis (Fu et al., ).…”
Section: Trophic Factorsmentioning
confidence: 99%